Sraya Banerjee1 1Research Scholar, Dept. of Journalism & Mass Communication, Berhampur University, (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
India's declining child sex ratio, rising incidence of female Foeticide and sex-selective abortions, and increased awareness of the practice may be partly due to the government's implementation of schemes and incentive programs designed to promote girls' and women's welfare. Female Foeticide is a form of gender discrimination that begins before birth and contributes to significant gender imbalances in countries like India and China. This study investigates the knowledge of female Foeticide among 100 women in Jhargram, West Bengal focusing on female health ideology and awareness campaigns. Data was collected through systematic random sampling and the method was survey. The research aims to understand the influence of female Foeticide on health and awareness. The study suggests that the government should take steps to raise awareness about female Foeticide through all health centres or self-help groups, so that every female in every village is understood separately about this matter and their families.If non-governmental organisations (NGOs) or health agencies attempted to explain these processes in villages and households using awareness camps, theatres, or audio-visual means, not only women but also families would understand these bio variables and avoid such problems.